Practical Wildlife Care - Stocker, Les. (Oxford, UK ; Ames, Iowa : Blackwell Pub., 2005)
"Following on from the major success of the first edition, this second edition provides even more useful information on wildlife care and rehabilitation. As well as covering a whole range of species, with sections on birds, mammals, reptiles and amphibians, this edition now includes information on many 'alien' species appearing in the British countryside such as wallabies, wild boar and exotic reptiles."--Jacket
1. Prime directives -- 2. First response -- 3. Fluid therapy / Part I: Building blocks -- 4. Fluid Therapy / Part II: Administration -- 5. Wound management / Part I: The biology of wounds -- 6. Wound management / Part II: The treatment of wounds -- 7. Biology and first aid of fractures -- 8. Fracture management -- 9. Avian wildlife disease -- 10. Mammalian wildlife disease -- 11. Garden birds -- 12. Pigeons -- 13. Game birds 14. Corvids -- 15. Water birds -- Ducks -- 16. Water birds -- Swans -- 17. Geese and other water birds -- 18. Birds of prey -- 19. Seabirds -- 20. Hand-rearing orphaned birds -- 21. Small mammals -- 22. Hedgehogs -- 23. Rabbits and hares -- 24. Red fox -- 25. Badgers -- Other mustelids 27. Deer -- 28. Bats -- 29. Other mammal species -- 30. Rearing orphaned wild mammals -- 31. Reptiles and amphibians -- Appendix 1. Bat Conservation Trust guidelines on handling bats -- Appendix 2. British Divers Marine Life Rescue (BDMLR) guidelines for response to cetacean strandings -- Appendix 3. Birds on schedule 4 of the Wildlife and Countryside Act 1981 (as of May 1998) -- Appendix 4. The law relating to the use and possession of airguns -- Appendix 5. Suggested record sheet to accompany bat samples to the central veterinary laboratory -- Appendix 6. Selected rehabilitation supplies and suppliers -- Appendix 7. Useful addresses in wildlife rehabilitation -- References and further reading -- Index.
Includes bibliographical references (pages 325-329) and index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Wildlife rehabilitation; Wildlife rescue; Wildlife diseases -- Treatment; First aid for animals; First aid in illness and injury; First Aid; Animals, Wild; NATURE -- Environmental Conservation & Protection; Erste Hilfe; Tiermedizin; Wildtiere; Wildtierkrankheit; Electronic books